The airline transport regulation and development of public health crisis in megacities of China - Li, Jiannan (J Transp Health, 2020)
BACKGROUND: The Civil Aviation Administration of China (CAAC) declares the airline transport regulation in January 2020 to help retard the spread of the novel coronavirus disease in China. This study is to examine the effect of airline transport regulation on confirmed cases of the novel coronavirus disease in megacities in China. METHODS: This study combines the multi-source data from the health data platform DXY, the airline data platform Airsavvi, the China Economic Internet Statistical Database and the China Railway website. The megacities whose airports have a passenger throughput of over 30 million per year (11 megacities: Wuhan, Beijing, Shanghai, Guangzhou, Chengdu, Shenzhen, Kunming, Xi'an, Chongqing, Hangzhou, Nanjing) are included in the analysis. The regression analysis is conducted in this study. RESULTS: The curvilinear relationship between the limitation on air traffic and confirmed cases of the novel coronavirus disease is identified (coefficient of the linear term = −4.650, p-value < 0.01; coefficient of the quadratic term = 4.089, p-value < 0.01). CONCLUSIONS: This study confirms the effectiveness of airline transport regulation in suppressing the development of this pandemic. The limitation on air traffic is found to negatively affect the confirmed cases in China's megacities. However, such effect marginally recedes as the strength of limitation intensifies. It suggests that comprehensive policy intervention is in need and air traffic can be one of important determinants that affect the epidemic development.